Garuda Wisnu Kencana: a piece of art, a part of history - I Made Ari Kapela (Bali Tourism Board, 2018)
Garuda Wisnu Kencana (GWK) in Ungasan Hill, South Kuta, BadungRegency is expected as a future tourism icon of Bali to attractdomestic and foreign tourists. Standing firmly in the area of 60hectares, with 121 meters high from base to peak, and 64 meters inwidth, make It as one of the largest and highest impressive figuresin the world. The initial idea to build the statue was firstly sparkedin 1989 when I Nyoman Nuarta met with Joop Ave. The projectbegan after received approval from President Soeharto in 1997.Some questions and critics from the scholar did not budge the plan.However, the monetary crisis and politic situation that hit Indonesiain 1998, postponed the construction of this enormous project. Theproject resumed in 2013 after I Nyoman Nuarta, met with The NingKing, the owner of PT Alam Sutera Realty. Alam Sutera acquiredthe project from PT Garuda Adimatra Indonesia. On September22, 2018, President Joko Widodo inaugurated the Garuda WisnuKencana Statue. In his speech, Joko Widodo expressed his delightto witness the work. The statue proved Indonesia is a great nationthat can give birth to a brand-new masterpiece. GWK Cultural Parkoffers not only a magnificent landmark but also countless touristattractions. There are daily Indonesian traditional music and dance,lodging area, shopping center, outbound facilities, dining area anda massive venue for high scale event.